2018
DOI: 10.3329/bjar.v43i2.37336
|View full text |Cite
|
Sign up to set email alerts
|

Increasing cropping intensity and productivity through mungbean inclusion in wheat-fallow-T. Aman rice cropping pattern

Abstract: The experiment was conducted at the farmers’ field of Bhaluka Upazilla under On-Farm Research division, Bangladesh Agricultural Research Institute, Mymensingh during 2014-15 and 2015-16 to evaluate the performance of Wheat-Mungbean-T.aman rice improved cropping pattern against a farmers cropping pattern of Wheat-Fallow-T.aman rice. The findings of the study indicated that three crops could be grown successfully in sequence in the tested site. The higher rice equivalent yield (15.33 t hd-1 yr.-1), production ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 3 publications
13
6
0
Order By: Relevance
“…Higher yield of rice possibly due to improved production technologies. Similar results were obtained by Mandal et al (2015), Nazrul et al (2017), Khan (2018). The improved cropping pattern produced higher amount of total by-product yield (18.74 t ha -1 ) than the farmers' existing pattern (15.49 t ha -1 ).…”
Section: Grain and By-product Yield Of Crops In Cropping Patternssupporting
confidence: 87%
“…Higher yield of rice possibly due to improved production technologies. Similar results were obtained by Mandal et al (2015), Nazrul et al (2017), Khan (2018). The improved cropping pattern produced higher amount of total by-product yield (18.74 t ha -1 ) than the farmers' existing pattern (15.49 t ha -1 ).…”
Section: Grain and By-product Yield Of Crops In Cropping Patternssupporting
confidence: 87%
“…Organic matter added to soil through incorporation of non-economic plant parts helped to maintain the quality of soil (Table 2). These results are supported by Mondal et al (2015) and Khan et al (2018) who found that inclusion of mungbean in the existing farmer's cropping pattern improve the soil fertility status. The newly introduced crop in the farmers existing pattern was garden pea in the Rabi season to use fallow period.…”
Section: Resultssupporting
confidence: 52%
“…Cropping intensification from single to double increase the system REY by two to four times higher in rice-based cropping system [28][29][30], even varied 9-34% from rice-rice to rice-non rice crop based cropping systems [31] in India. Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%